A study on characteristics of sediment feature of mangrove - Saruga, S.; Sivashanthini, K.; Sutharshiny, S. (University of Jaffna, 2018)
This paperemphasize the major sediment characteristics of mangrove ecosystem. For this survey two locations such as Sarasaalai and Kapputhu were chosen. Grain-size distribution, physicochemical parameters and organic matter content of surface soil were analyzed. Mangrove soil were sampled in the second week each month from June 2016 to November 2016. Triplicate samples at each sites were collected by mud sampler. The pH, electrical conductivity and salinity of surface soil were measured by pH, electrical conductivity and salinity probe respectively. Dried soil sample were examined for organic matter content and grain-size distribution. In the month of September high amount of salinity and electrical conductivity were observed which are shown asimilar trend. Higher amount of organic matter was found in Sarasaalai mangrove region. The periodic re-suspension of sediments probably was largely responsible for the high organic matter in mangrove ecosystem. The soil is dominated by sandy sediment with mean grain-size of 0.05mm to 2mm.The present study would form a useful tool for further ecological assessment and monitoring of soil characteristics of Sarasaalai and Kapputhu mangroves.
Keywords: Grain size; Mangrove; Organic matter; Physicochemical parameter; Sediment